2021
DOI: 10.3390/ijerph18041892
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Socioeconomic Status, Handgrip Strength, and Non-Alcoholic Fatty Liver Disease in Middle-Aged Adults

Abstract: Although low socioeconomic status (SES) and decreased muscle strength have been found to be associated with the risk factors of non-alcoholic fatty liver disease (NAFLD), including insulin resistance, obesity, and metabolic syndrome, the associations among SES, muscle strength, and NAFLD are still unclear. We aimed to investigate the combined effect of SES and relative handgrip strength (HGS) on the risk of NAFLD in middle-aged adults. Data from 5272 middle-aged adults who participated in the Korea National He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 41 publications
(54 reference statements)
3
37
0
Order By: Relevance
“…Nine studies analyzed the association between Mediterranean diet, physical activity, and NAFLD; four of them studied recruited people as a single group [ 22 , 25 , 29 , 30 ], two classified participants into two groups [ 24 , 31 ], two analyzed hand-grip strength [ 32 , 33 ], and one assessed renal outcomes [ 26 ]. Most studies agreed that a Mediterranean diet and physical activity improved all or some of NAFLD risk factors: weight reduction [ 22 , 29 , 30 ], body mass index [ 24 , 29 , 30 ], waist circumference [ 24 , 29 , 30 ], triglyceridemia [ 22 , 29 ], LDL-cholesterol [ 29 , 30 , 31 ], impaired fasting glycemia [ 22 , 29 ], visceral adipose index and fatty liver index [ 29 ], lipid accumulation [ 14 , 29 ], homeostatic model assessment-insulin resistance [ 29 , 30 , 31 ]; increased HDL-cholesterol [ 22 , 29 ]; normalization of alanine aminotransferase [ 22 , 29 , 30 ]; reduction of gamma glutamyl transferase [ 30 ]; and improvement of steatosis [ 24 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies analyzed the association between Mediterranean diet, physical activity, and NAFLD; four of them studied recruited people as a single group [ 22 , 25 , 29 , 30 ], two classified participants into two groups [ 24 , 31 ], two analyzed hand-grip strength [ 32 , 33 ], and one assessed renal outcomes [ 26 ]. Most studies agreed that a Mediterranean diet and physical activity improved all or some of NAFLD risk factors: weight reduction [ 22 , 29 , 30 ], body mass index [ 24 , 29 , 30 ], waist circumference [ 24 , 29 , 30 ], triglyceridemia [ 22 , 29 ], LDL-cholesterol [ 29 , 30 , 31 ], impaired fasting glycemia [ 22 , 29 ], visceral adipose index and fatty liver index [ 29 ], lipid accumulation [ 14 , 29 ], homeostatic model assessment-insulin resistance [ 29 , 30 , 31 ]; increased HDL-cholesterol [ 22 , 29 ]; normalization of alanine aminotransferase [ 22 , 29 , 30 ]; reduction of gamma glutamyl transferase [ 30 ]; and improvement of steatosis [ 24 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…High hand-grip strength was associated with a decreased risk of NAFLD [ 33 ]. Moreover, NAFLD indexes, such as a simple NAFLD score, hepatic steatosis index, NAFLD fibrosis score, and fibrosis 4 calculator, decreased linearly when hand-grip strength increased [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, NAFLD prevalence seems to be higher among individuals with lower socioeconomic position in Western countries [33,34]. However, data coming from Eastern countries is not so consistent [35,36]. A study conducted in South Korea found that people with a low socioeconomic status have a significantly higher risk of developing NAFLD (OR 1.7) [36].…”
Section: Socioeconomic Position/statusmentioning
confidence: 99%
“…However, data coming from Eastern countries is not so consistent [35,36]. A study conducted in South Korea found that people with a low socioeconomic status have a significantly higher risk of developing NAFLD (OR 1.7) [36]. A Chinese study also found that people with a higher median income had a 1.96 higher risk of developing NAFLD than the low-income population [35].…”
Section: Socioeconomic Position/statusmentioning
confidence: 99%
See 1 more Smart Citation